Species diversity of Polychaete in coral reef ecosystem of Great Nicobar Island, India - V. SEKAR; R. RAJASEKARAN; V. SACHITHANANDAM; R. SANKAR; R. SRIDHAR; PAUL W. KINGSLEY (Smujo International, 2016)
Abstract. Sekar V Rajasekaran R, Sachithanandam V, Sankar R, Sridhar R, Kingsley PW. 2016. Species diversity of Polychaete in coral reef ecosystem of Great Nicobar Island, India. Nusantara Bioscience 8: 71-76. Cryptofauna inhabiting the shelves of the coral reefs in Great Nicobar Islands are affected by bio-erosion caused by grazing and boring of organisms, hence present study revealed on two major components the opportunistic and true borers. Samples were collected from four stations from three different coral types (live coral, highly degraded & rubble) of the Great Nicobar Islands. Of the total 401 individuals of Polychaetes collected from various sites 8 taxonomic species namely Terebella ehrenbergi, Idanthyrsus pennatus, Lysidice ninetta, L. collaris, Pseudonereis variegata, Perinereis cultrifera, P. nigropunctata, Eurythoe complanata were identified from the aforementioned three coral type sources. Among these P. variegata and L. collaris which accounted for 32.01% and 28.5% respectively, were the most dominant cryptic groups; whereas I. pennatus and T. ehrenbergi were the least records in all three habitats which accounted for 1.75%. In this study, the observations revealed that degraded corals were found in greater abundance than rubble and live corals. The species composition was observed maximum in Laxmi Nagar due to the availability of degraded coral patches than other stations. The study to evaluates the baseline knowledge of the coral inhabiting Polychaete distribution, it would be a pathway for forthcoming researchers on particular group taxonomy, and towards better understanding and utilization of coral reef ecosystem of the Great Nicobar Islands.